Hemostatic Changes Associated With Increased Mortality Rates in Hospitalized Patients With HIV-Associated Tuberculosis: A Prospective Cohort Study - Janssen, Saskia (J Infect Dis, 2017)
BACKGROUND: Mortality rates remain high for human immunodeficiency virus (HIV)–associated tuberculosis, and our knowledge of contributing mechanisms is limited. We aimed to determine whether hemostatic changes in HIV-tuberculosis were associated with mortality or decreased survival time and the contribution of mycobacteremia to these effects. METHODS: We conducted a prospective study in Khayelitsha, South Africa, in hospitalized HIV-infected patients with CD4 cell counts <350/µL and microbiologically proved tuberculosis. HIV-infected outpatients without tuberculosis served as controls. Plasma biomarkers reflecting activation of procoagulation and anticoagulation, fibrinolysis, endothelial cell activation, matricellular protein release, and tissue damage were measured at admission. Cox proportional hazard models were used to assess variables associated with 12-week mortality rates. RESULTS: Of 59 patients with HIV-tuberculosis, 16 (27%) died after a median of 12 days (interquartile range, 0–24 days); 29 (64%) of the 45 not receiving anticoagulants fulfilled criteria for disseminated intravascular coagulation. Decreased survival time was associated with higher concentrations of markers of fibrinolysis, endothelial activation, matricellular protein release, and tissue damage and with decreased concentrations for markers of anticoagulation. In patients who died, coagulation factors involved in the common pathway were depleted (factor II, V, X), which corresponded to increased plasma clotting times. Mycobacteremia modestly influenced hemostatic changes without affecting mortality. CONCLUSIONS: Patients with severe HIV-tuberculosis display a hypercoagulable state and activation of the endothelium, which is associated with mortality.